Islamic Architecture through Western Eyes: Spain, Turkey, India and Persia - Greenhalgh, Michael, author.
1 online resource
Keywords: This book, the first of three, offers an anthology of Western descriptions of Islamic religious buildings of Spain, Turkey, India and Persia, mostly from the seventeenth to early twentieth centuries, taken from books and ambassadorial reports. As travel became easier and cheaper, thanks to viable roads, steamships, hotels and railways, tourist numbers increased, museums accumulated eastern treasures, illustrated journals proliferated, and photography provided accurate data. The second volume covers some of the religious architecture of Syria, Egypt and North Africa, while the third deals with Islamic palaces around the Mediterranean. All three deal with the impact of Western trade, taste and imports on the East, and examine the encroachment of westernised modernism, judged responsible for the degradation of Islamic styles.